Can't Take My Eyes Off of You: Eye Tracking Reveals How Ruminating Young Adolescents Get Stuck. Issue 6 (2nd November 2017) - Hilt, Lori M.; Leitzke, Brian T.; Pollak, Seth D.
Abstract : Rumination, a cognitive process that involves passively, repetitively focusing on negative feelings and their meaning, is a transdiagnostic risk factor for psychopathology. Research with adults has suggested that attentional control difficulties may underlie rumination, but questions remain about the nature of these processes. Furthermore, the relationship between attentional control and rumination in youth has received little empirical examination. In the present study, 92 youth (ages 9–14; 72% girls; 74% Caucasian) reported on their trait rumination and internalizing symptoms. They also completed a 1, 500 ms emotional-faces dot-probe task while their eye movements were measured to examine overt visual attention with high temporal precision. Youth's rumination was associated with greater dwell on emotional faces but not with initial orientation. These findings suggest that rumination is associated with increased attention to emotional information during the later stages of selective attention rather than earlier orienting to emotional cues. Implications for prevention and treatment of psychopathology are discussed.